Empowering Students in Drug-Emergency Preparedness through the Think-Pair-Share Learning Model in Samarinda (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Drug use is a problem for today's youth. Several factors contribute to this, including biological, psychological, and social development. One way to address this is by improving adolescents' cognitive skills through the Think-Pair-Share model. In this health program, the team combined TPS with BLS practices. The sample for this activity was 30 students from SMA N 3 Samarinda. The results showed an increase in their knowledge, attitudes, actions, skills, and values related to substance use with a p-value